The ribs of Eupatorieae (Asteraceae): of wide taxonomic value or reliable characters only among certain groups? - Marzinek, Juliana; De-Paula, Orlando Cavalari [UNESP]; Trombert Oliveira, Denise Maria (Springer Wien, 2010)
Rib numbers have traditionally been used in identification keys of Eupatorieae. Some species, however, demonstrate variations in this character much greater than those registered in the literature, making the use of this trait controversial. The large variations seen among some species of Eupatorieae examined in this work were found to be related to the fact that rib number is more closely associated with the pressure exerted by neighboring flowers on the capitulum than with genetic factors. According to our results, ribs are not a reliable taxonomic character for broad use in Eupatorieae, being especially inappropriate for Chromolaena stachyophylla, Praxelis pauciflora, and Vittetia orbiculata. The association between the occurrence of vascular bundles and ribs is also discussed, and the variability seen in some Eupatorieae is analyzed. Our data indicate that the formation of the ribs on the cypselae is determined more by the position occupied by the flower on the inflorescence than by the occurrence of vascular bundles.
Keywords: Rib; Vascular bundle; Eupatorieae; Asteraceae; Cypselae